An electromagnetic shielding composite material and its preparation method and application
By using MXene, meta-aramid chopped fibers and cationized meta-aramid precipitated fibers in electromagnetic shielding materials, combined with wet molding and hot pressing treatment, the problem of insufficient performance of existing electromagnetic shielding materials is solved, and a high-performance electromagnetic shielding composite material is realized.
Patent Information
- Application Number
- CN202311277404.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-09-28
AI Technical Summary
The applicability of existing electromagnetic shielding materials in refined and miniaturized electronic devices is limited, and the bonding strength between conductive materials and fibers is low, resulting in generally poor electromagnetic shielding performance.
MXene is used as the conductive material, chopped fibers of meta-aramid are used as the skeleton material, and precipitated fibers of cationized meta-aramid are used as the bonding material. The conductive and electromagnetic shielding properties of the material are improved by wet molding and hot pressing.
The conductivity and electromagnetic shielding performance of electromagnetic shielding composite materials are significantly improved, the strength of the material is enhanced, and the retention and uniform dispersion of MXene are improved.
Smart Images

Figure CN117229630B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electromagnetic shielding materials, and in particular relates to an electromagnetic shielding composite material and a preparation method and application thereof. Background Art
[0002] At present, traditional electromagnetic shielding materials are mostly metals or metal-based composite materials. Although they have high electromagnetic shielding effectiveness, their high density defect greatly reduces their applicability in sophisticated and miniaturized electronic devices, resulting in limited application scenarios. In order to reduce and eliminate the impact of electromagnetic waves on life and production, in order to match sophisticated electronic equipment.
[0003] Currently, electromagnetic shielding materials are obtained by compounding conductive materials with fiber materials. However, the bonding strength between the conductive material and the fiber in the composite material is low, and the retention rate of the conductive material is low, resulting in generally poor electromagnetic shielding performance of the composite material. Therefore, there is an urgent need for a high-performance electromagnetic shielding material that adapts to modern development and has important social significance. Summary of the invention
[0004] In view of the technical problems existing in the prior art, the present invention provides an electromagnetic shielding composite material and a preparation method and application thereof, so as to solve the technical problem that the electromagnetic shielding performance of the existing electromagnetic shielding materials is generally poor.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] The present invention provides a method for preparing an electromagnetic shielding composite material, comprising the following steps:
[0007] Performing cationization treatment on the fibrid of meta-aramid fiber to obtain cationized fibrid of meta-aramid fiber;
[0008] The MXene dispersion, the chopped fibers of meta-aramid and the precipitated fibers of the cationic meta-aramid are mixed, and then deflaking, wet forming, cold pressing, vacuum drying and hot pressing are performed in sequence to obtain the electromagnetic shielding composite material.
[0009] Furthermore, the chopped meta-aramid fibers are cleaned chopped meta-aramid fibers;
[0010] The process of obtaining the cleaned chopped meta-aramid fibers is as follows:
[0011] Sodium dodecylbenzene sulfonate is used to clean the sizing agent remaining in the production of meta-aramid chopped fibers, and the cleaned meta-aramid chopped fibers are obtained after drying.
[0012] Further, the process of cationizing the meta-aramid fibrid to obtain the cationized meta-aramid fibrid is as follows:
[0013] The fibrids of meta-aramid are dispersed in an aqueous solution of polydiallyldimethylammonium chloride, and then are dispersed, filtered and dried to obtain the cationized fibrids of meta-aramid.
[0014] Furthermore, the preparation process of the MXene dispersion is as follows:
[0015] Mixing lithium fluoride, hydrochloric acid solution and Ti3AlC2 to perform an etching reaction to obtain a mixed solution after the reaction;
[0016] Washing and centrifuging the mixed solution after the reaction several times to remove the supernatant until the pH value reaches neutral, thereby obtaining a neutral solution;
[0017] The central solution is subjected to ultrasonic treatment and centrifugation to obtain the MXene dispersion.
[0018] Furthermore, when the MXene dispersion, the cleaned chopped fibers of meta-aramid and the cationized meta-aramid fibrids are mixed, the process is as follows:
[0019] Mixing the MXene dispersion and the meta-aramid fiber in a mass ratio of (75-85):(25-15);
[0020] Wherein, the concentration of the MXene dispersion is 4 mg / mL;
[0021] The meta-aramid fiber includes the cleaned chopped meta-aramid fiber and the cationized meta-aramid fiber precipitate, and the mass ratio of the cleaned chopped meta-aramid fiber to the cationized meta-aramid fiber precipitate is (5-2):(5-8).
[0022] Furthermore, during the cold pressing process, the cold pressing pressure is 0.3-0.6 MPa and the cold pressing time is 5-10 min.
[0023] Furthermore, during the hot pressing treatment, the hot pressing pressure is 5-15 MPa, the hot pressing temperature is 180-220° C., and the time is 5-11 min.
[0024] The present invention also provides an electromagnetic shielding composite material, which is prepared by using the preparation method of the electromagnetic shielding composite material.
[0025] Furthermore, the density of the electromagnetic shielding composite material is 1.1-1.15 g / cm 3; The electrical conductivity of the electromagnetic shielding composite material is 35-2050S / m; in the X-band, the electromagnetic shielding effectiveness of the electromagnetic shielding composite material is 15-36dB.
[0026] The present invention also provides an application of an electromagnetic shielding composite material, wherein the electromagnetic shielding composite material is used as an electromagnetic shielding material in electronic equipment.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention provides an electromagnetic shielding composite material and a preparation method and application thereof. MXene is selected as a conductive material, short-cut meta-aramid fibers are used as a skeleton material, and cationized fibrils of meta-aramid fibers are used as a bonding material. A composite material with excellent conductivity is obtained by wet molding, and the composite material is subjected to a hot pressing treatment to make the MXene in the composite material more tightly combined, thereby effectively improving the conductivity and electromagnetic shielding performance of the material. Secondly, the hot pressing treatment effectively improves the interface bonding strength between the short-cut meta-aramid fibers and the fibrils, and between the MXene and the short-cut meta-aramid fibers or the fibrils, thereby effectively improving the strength of the electromagnetic shielding material. In addition, since the surface of the cationized meta-aramid fibrils carries a positive charge, an electrostatic adsorption effect can be generated between the cationized meta-aramid fibrils and the negatively charged MXene during the fiber debonding process, thereby uniformly adsorbing the MXene on the surface of the meta-aramid fibrils, effectively improving the retention rate of the MXene during the wet forming process; in addition, the cationized meta-aramid fibrils obtained by modification that adsorb MXene can uniformly disperse the MXene in the slurry system during the wet forming process, and the MXene can be uniformly dispersed in the paper after papermaking, effectively improving the multiple reflections of electromagnetic waves during propagation inside the electromagnetic shielding material, and effectively improving the electromagnetic shielding effectiveness of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 SEM images of MXene in Examples 1-4.
[0030] Figure 2 This is a surface SEM image of the electromagnetic shielding composite material prepared in Example 2;
[0031] Figure 3 This is a cross-sectional SEM image of the electromagnetic shielding composite material prepared in Example 3. DETAILED DESCRIPTION
[0032] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail in the following specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0033] The present invention provides a method for preparing an electromagnetic shielding composite material, comprising the following steps:
[0034] Step 1, preparing a MXene dispersion; specifically, mixing lithium fluoride, hydrochloric acid solution and Ti3AlC2, performing an etching reaction, and obtaining a mixed solution after the reaction; washing and centrifuging the mixed solution after the reaction several times to remove the supernatant until the pH value reaches neutral, and obtaining a neutral solution; ultrasonically treating and centrifuging the central solution to obtain the MXene dispersion.
[0035] Step 2: using sodium dodecylbenzene sulfonate to clean the sizing agent remaining in the production of the meta-aramid chopped fibers, and obtaining the cleaned meta-aramid chopped fibers after drying.
[0036] Step 3, cationizing the meta-aramid fiber to obtain cationized meta-aramid fiber; specifically, dispersing the meta-aramid fiber in an aqueous solution of polydiallyldimethylammonium chloride, and then performing delamination, filtering and drying to obtain the cationized meta-aramid fiber.
[0037] Step 4: Mix the MXene dispersion, the chopped fibers of meta-aramid and the cationized meta-aramid fibers, and then sequentially perform delamination, wet forming, cold pressing, vacuum drying and hot pressing to obtain the electromagnetic shielding composite material.
[0038] In the present invention, when the MXene dispersion, the cleaned chopped fibers of meta-aramid and the cationized meta-aramid fibrids are mixed, the process is as follows:
[0039] A MXene dispersion and meta-aramid fibers are mixed in a mass ratio of (75-85):(25-15); wherein the concentration of the MXene dispersion is 0.4 mg / mL; the meta-aramid fibers include the cleaned chopped meta-aramid fibers and the cationized meta-aramid fibrils, and the mass ratio of the cleaned chopped meta-aramid fibers to the cationized meta-aramid fibrils is (5-2):(5-8).
[0040] In the present invention, during the cold pressing treatment, the cold pressing pressure is 0.3-0.6MPa and the cold pressing time is 5-10min; during the hot pressing treatment, the hot pressing pressure is 5-15MPa, the hot pressing temperature is 180-220°C and the time is 5-11min.
[0041] Preparation principle:
[0042] The electromagnetic shielding material and preparation method thereof described in the present invention select MXene nanosheets with excellent electrochemical and mechanical properties as conductive materials, use meta-aramid chopped fibers as skeleton materials, and use cationized meta-aramid fibrils as bonding materials, and form them into paper through wet process to obtain a composite material with excellent conductivity; after hot pressing, the MXene nanosheets are more tightly bonded, and the conductivity and electromagnetic shielding performance are effectively improved; secondly, the interface bonding strength between the chopped fibers and the fibrils and between the MXene nanosheets and the chopped fibers or the fibrils after hot pressing is also effectively improved; therefore, the strength of the electromagnetic shielding composite material is also greatly improved; secondly, the surface of the fibrils of the cationized meta-aramid carries a positive charge, and the negatively charged MXene nanosheets can be evenly adsorbed on the surface of the fibrils of the meta-aramid during the fiber debonding process by electrostatic adsorption, which greatly improves the retention rate of the MXene nanosheets during the wet forming process; wherein, compared with the traditional process, The retention rate of nano-scale materials in the process is increased from 10% to 30% to more than 99%, which effectively solves the problem that the traditional wet forming of paper cannot retain nano-scale materials, and provides a new way for wet forming papermaking; in addition, the precipitated fibers of the modified cationic meta-aramid fiber adsorb MXene nanosheets to achieve the wet forming process, and the MXene nanosheets are evenly dispersed in the slurry system. After the paper is formed, the MXene nanosheets can be evenly dispersed in the paper, avoiding the MXene nanosheets deposited under the paper during the wet forming process to cause the difference between the two sides, resulting in different conductivity on both sides of the paper, or even non-conductive phenomenon on one side, effectively ensuring the conductive performance and electromagnetic shielding effectiveness of the composite material; in addition, the MXene evenly dispersed in the paper can improve the multiple reflections of electromagnetic waves when propagating in the paper, effectively improving the electromagnetic shielding performance of the paper, so as to meet its applicability in refined and miniaturized electronic devices; wherein, the density of the electromagnetic shielding composite material is 1.1-1.15g / cm 3 ; The electrical conductivity of the electromagnetic shielding composite material is 35-2050S / m; in the X-band (8.2-12.4GHz), the electromagnetic shielding effectiveness of the electromagnetic shielding composite material is 15-36dB.
[0043] Example 1
[0044] This embodiment 1 provides a method for preparing an electromagnetic shielding composite material, comprising the following steps:
[0045] Step 1: Mix 1 g of Ti3AlC2, 1.6 g of lithium fluoride (LiF) and 25 ml of hydrochloric acid solution, and stir magnetically at 35°C for 48 hours to perform an etching reaction to obtain a mixed solution after the reaction; wherein the mass percentage of the hydrochloric acid solution is 37%, and the mesh size of the Ti3AlC2 is 400 mesh.
[0046] Step 2: Wash the mixed solution after the reaction several times and centrifuge it to remove the supernatant until the pH value reaches neutral to obtain a neutral solution; ultrasonically treat and centrifuge the central solution, collect the upper dark green dispersion, and obtain the MXene dispersion; wherein, during the centrifugal treatment, the centrifugal speed is 3500r / min, and the centrifugal time is 5min; during the ultrasonic treatment, the ultrasonic power is 80W, and the ultrasonic time is 30min.
[0047] Step 3: using sodium dodecylbenzene sulfonate (SDBS) to clean the sizing agent remaining during the production of the meta-aramid chopped fibers, and obtaining the cleaned meta-aramid chopped fibers after drying.
[0048] Step 4, dispersing the precipitated fibrils of meta-aramid in an aqueous solution of polydiallyldimethylammonium chloride (PDDA), and then defibrating, filtering and air-drying for 12 hours to obtain the precipitated fibrils of the cationic meta-aramid; wherein the mass concentration of the aqueous solution of polydiallyldimethylammonium chloride is 3wt%; during the defibrating process, the fiber defibrating machine is used, and the defibrating speed is 40000r / min.
[0049] Step 5: Mix the MXene dispersion in step 2, the chopped fibers of the meta-aramid fiber washed in step 3, and the precipitated fibers of the cationized meta-aramid fiber in step 4, and then perform delamination, wet forming, cold pressing, vacuum drying, and hot pressing treatment in sequence to obtain the electromagnetic shielding composite material.
[0050] It should be noted that the concentration of the MXene dispersion is 0.4 mg / mL; when the MXene dispersion, the cleaned chopped fibers of meta-aramid and the cationized meta-aramid fibrils are mixed, specifically: the MXene dispersion and the meta-aramid fibers are mixed in a mass ratio of 70:30; wherein the meta-aramid fibers include the cleaned chopped fibers of meta-aramid and the cationized meta-aramid fibrils, and the mass ratio of the cleaned chopped fibers of meta-aramid to the cationized meta-aramid fibrils is 5:5; during the cold pressing treatment, the cold pressing pressure is 0.3 MPa and the cold pressing time is 10 min; during the hot pressing treatment, the hot pressing pressure is 5 MPa, the hot pressing temperature is 180°C, and the time is 11 min; during vacuum drying, the drying temperature is 105°C and the drying time is 8 min.
[0051] Performance test results description:
[0052] The conductivity and electromagnetic shielding effectiveness of the electromagnetic shielding composite material prepared in this Example 1 were tested, and the test results showed that: the electromagnetic shielding composite material has high conductivity and electromagnetic shielding effectiveness; wherein, the conductivity of the electromagnetic shielding composite material is 2050S / m, and the electromagnetic shielding effectiveness is 36dB.
[0053] Example 2
[0054] The preparation method of an electromagnetic shielding composite material provided in this embodiment 2 is basically the same as the preparation method described in embodiment 1, except that:
[0055] In step 4, the mass concentration of the aqueous solution of polydiallyldimethylammonium chloride is 2 wt %; during the decomposition process, the decomposition speed is 30000 r / min; and the air-drying treatment is performed for 18 hours.
[0056] In step 5, the concentration of the MXene dispersion is 0.4 mg / mL; the MXene dispersion and the meta-aramid fiber are mixed in a mass ratio of 75:25; wherein the mass ratio of the cleaned chopped meta-aramid fiber to the cationized meta-aramid precipitated fiber in the meta-aramid fiber is 4:6; during the cold pressing treatment, the cold pressing pressure is 0.4 MPa and the cold pressing time is 8 min; during the hot pressing treatment, the hot pressing pressure is 5 MPa, the hot pressing temperature is 190°C, and the time is 9 min; during vacuum drying, the drying temperature is 105°C and the drying time is 10 min.
[0057] Performance test results description:
[0058] The conductivity and electromagnetic shielding effectiveness of the electromagnetic shielding composite material prepared in Example 2 were tested. The test results showed that the conductivity of the electromagnetic shielding composite material was 420 S / m, and the electromagnetic shielding effectiveness was 27 dB.
[0059] Example 3
[0060] The preparation method of an electromagnetic shielding composite material provided in this embodiment 3 is basically the same as the preparation method described in embodiment 1, except that:
[0061] In step 4, the mass concentration of the aqueous solution of polydiallyldimethylammonium chloride is 1wt%; during the decomposition process, the decomposition speed is 20000r / min; and the air-drying treatment is performed for 24h.
[0062] In step 5, the concentration of the MXene dispersion is 0.4 mg / mL; the MXene dispersion and the meta-aramid fiber are mixed in a mass ratio of 80:20; wherein the mass ratio of the cleaned chopped meta-aramid fiber to the cationized meta-aramid precipitated fiber in the meta-aramid fiber is 3:7; during the cold pressing treatment, the cold pressing pressure is 0.5 MPa and the cold pressing time is 6 min; during the hot pressing treatment, the hot pressing pressure is 5 MPa, the hot pressing temperature is 200°C, and the time is 7 min; during vacuum drying, the drying temperature is 115°C and the drying time is 12 min.
[0063] Performance test results description:
[0064] The conductivity and electromagnetic shielding effectiveness of the electromagnetic shielding composite material prepared in Example 3 were tested. The test results showed that the conductivity of the electromagnetic shielding composite material was 131 S / m, and the electromagnetic shielding effectiveness was 22.5 dB.
[0065] Example 4
[0066] The preparation method of an electromagnetic shielding composite material provided in this embodiment 4 is basically the same as the preparation method described in embodiment 1, except that:
[0067] In step 4, the mass concentration of the aqueous solution of polydiallyldimethylammonium chloride is 1wt%; during the decomposition process, the decomposition speed is 20000r / min; and the air-drying treatment is performed for 30h.
[0068] In step 5, the concentration of the MXene dispersion is 0.4 mg / mL; the MXene dispersion and the meta-aramid fiber are mixed in a mass ratio of 85:15; wherein the mass ratio of the cleaned chopped meta-aramid fiber to the cationized meta-aramid precipitated fiber in the meta-aramid fiber is 2:8; during the cold pressing treatment, the cold pressing pressure is 0.6 MPa and the cold pressing time is 5 min; during the hot pressing treatment, the hot pressing pressure is 5 MPa, the hot pressing temperature is 220°C, and the time is 5 min; during vacuum drying, the drying temperature is 120°C and the drying time is 14 min.
[0069] Performance test results description:
[0070] The conductivity and electromagnetic shielding effectiveness of the electromagnetic shielding composite material prepared in Example 4 were tested. The test results showed that the conductivity of the electromagnetic shielding composite material was 35 S / m, and the electromagnetic shielding effectiveness was 15 dB.
[0071] As attached Figure 1 As shown, attached Figure 1 The SEM images of MXene in Examples 1-4 are given in the attached Figure 1It can be seen that lithium fluoride and hydrochloric acid solution can etch Ti3AlC2 well and make it present a loose accordion state, providing necessary conditions for the next ultrasonic dispersion; as shown in the attached Figure 2 As shown, attached Figure 2 The surface SEM image of the electromagnetic shielding composite material prepared in Example 2 is given in the figure. Figure 2 It can be seen from the figure that the surface of the electromagnetic shielding composite material is dense and has no pores, which is conducive to forming a better conductive network and improving conductivity; Figure 3 As shown, attached Figure 3 The cross-sectional SEM image of the electromagnetic shielding composite material prepared in Example 3 is given in the attached Figure 3 It can be seen that there is no pore in the cross section of the electromagnetic shielding composite material, which means that the interior of the composite material is also very dense after hot pressing, which effectively reduces the thickness of the material, improves the electrical conductivity of the material, and thus improves the electromagnetic shielding performance.
[0072] The electromagnetic shielding composite material and the preparation method thereof described in the present invention select MXene as the conductive material. MXene is a two-dimensional nanomaterial with small powder volume, large specific surface area and excellent conductive performance. Short-cut fibers of meta-aramid are used as the skeleton material, and cationized meta-aramid precipitated fibers are used as the bonding material. Among them, meta-aramid fiber is a high-performance fiber with light weight, high strength, high modulus, high temperature resistance, acid and alkali resistance, and structural designability, which is widely used in aerospace, transportation and electrical fields. Thanks to the excellent performance of meta-aramid fiber, it can be used as a reinforcing material and base material for composite materials. A composite material with excellent conductivity is obtained by wet molding, and hot pressing treatment is performed to make the MXene in the composite material more tightly combined to obtain the electromagnetic shielding composite material. The preparation process of the present invention is simple, the electromagnetic shielding composite material has excellent conductivity and electromagnetic shielding effectiveness, and the material strength is relatively high.
[0073] The above embodiment is only one of the implementation methods that can realize the technical solution of the present invention. The scope of protection claimed by the present invention is not limited only to this embodiment, but also includes changes, replacements and other implementation methods that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed by the present invention.
Claims
1. A method for preparing an electromagnetic shielding composite material, characterized in that: The following steps are involved: Performing cationization treatment on the fibrid of meta-aramid fiber to obtain cationized fibrid of meta-aramid fiber; The MXene dispersion, the short-cut fibers of meta-aramid and the cationized meta-aramid fibrils are mixed, and then the mixture is sequentially subjected to deflaking, wet forming, cold pressing, vacuum drying and hot pressing to obtain the electromagnetic shielding composite material; The process of cationizing the meta-aramid fibrid to obtain the cationic meta-aramid fibrid is as follows: Dispersing the fibrids of meta-aramid fiber in an aqueous solution of polydiallyldimethylammonium chloride, followed by delamination, filtering and drying to obtain the cationized fibrids of meta-aramid fiber; The chopped meta-aramid fibers are cleaned chopped meta-aramid fibers; The process of obtaining the cleaned chopped meta-aramid fibers is as follows: Sodium dodecylbenzene sulfonate is used to clean the sizing agent remaining in the production of meta-aramid chopped fibers, and the cleaned meta-aramid chopped fibers are obtained after drying; When the MXene dispersion, the cleaned chopped fibers of meta-aramid and the cationized meta-aramid fibrids are mixed, the steps are as follows: Mix the MXene dispersion and the meta-aramid fiber in a mass ratio of (75-85):(25-15); Wherein, the concentration of the MXene dispersion is 4 mg / mL; The meta-aramid fibers include the cleaned chopped meta-aramid fibers and the cationized meta-aramid fibrils, and the mass ratio of the cleaned chopped meta-aramid fibers to the cationized meta-aramid fibrils is (5-2):(5-8).
2. The method for preparing an electromagnetic shielding composite material according to claim 1, characterized in that: The preparation process of the MXene dispersion is as follows: Mixing lithium fluoride, hydrochloric acid solution and Ti3AlC2 to perform an etching reaction to obtain a mixed solution after the reaction; Washing and centrifuging the mixed solution after the reaction several times to remove the supernatant until the pH value reaches neutral, thereby obtaining a neutral solution; The neutral solution is subjected to ultrasonic treatment and centrifugation to obtain the MXene dispersion.
3. The method for preparing an electromagnetic shielding composite material according to claim 1, characterized in that: During the cold pressing process, the cold pressing pressure is 0.3-0.6MPa and the cold pressing time is 5-10min.
4. The method for preparing an electromagnetic shielding composite material according to claim 1, characterized in that: During the hot pressing treatment, the hot pressing pressure is 5-15MPa, the hot pressing temperature is 180-220°C, and the time is 5-11min.
5. An electromagnetic shielding composite material, characterized in that: The electromagnetic shielding composite material is prepared by the preparation method of any one of claims 1 to 4.
6. The electromagnetic shielding composite material according to claim 5, characterized in that: The density of the electromagnetic shielding composite material is 1.1-1.15 g / cm 3 ; The electrical conductivity of the electromagnetic shielding composite material is 35-2050S / m; in the X-band, the electromagnetic shielding effectiveness of the electromagnetic shielding composite material is 15-36dB.
7. Use of an electromagnetic shielding composite material as claimed in claim 5 or 6, characterized in that: The electromagnetic shielding composite material is used as an electromagnetic shielding material in electronic equipment.
Citation Information
Patent Citations
Preparation method of layer-by-layer self-assembled semiconductor fiber and transistor sensor
CN113897785A
Preparation method of flexible electromagnetic shielding material based on compounding of two-dimensional titanium carbide (MXene) and aramid fiber
CN114635282A
Conductive polymer coated MXene-SiC-high polymer composite fiber wave-absorbing material and preparation method thereof
CN114874752A
Meta-aramid functional paper as well as preparation method and application thereof
CN116657443A